PENGARUH WORD OF MOUTH, KESADARAN MEREK DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN - Putri Dwi Cahyani; Nadia Utami; Sekar Bibit Lestari (Valuasi : Jurnal Ilmiah Ilmu Manajemen dan Kewirausahaan, 2022)
This study aims to determine whether there is an influence of Word of Mouth (x1), Brand awareness (x2) and product quality (x3) on purchasing decisions (y) on Consumers of Mie Gacoan in Yogyakarta.  This research is a quantitative research, using descriptive analysis. By sampling using the nonprobability sampling technique method with questionnaire instruments. Meanwhile, the data retrieval technique uses purposive sampling. The sample in this study was 122 respondents calculated by the ancient rao formula. Analyzed using multiple regression analysis. The results showed that the Word Of Mouth variable (x1) had no influence on the purchase decision (y) as evidenced by the significance value of 0.395 > 0.05 and the T-count value of -0.853 < the T-table value of 1.980 then Ho1 was accepted and Ha1 was rejected. And there is an effect of Brand Awareness (x2) on the Purchase decision (y) the significance value of 0.000 < 0.05 and the T-count value of 5.679 > T-table 1.980 then Ho1 is rejected and Ha2 is accepted. And there is an effect of Product Quality (x3) on purchasing decision (y) with a significance value of 0.000 < 0.05 and a T-count value of 8.230 > T-table 1.980, then Ho1 is rejected and Ha2 is accepted. And from the results of the coefficient of determination analysis test, it is known that the value of R Square is 0.747, this means that the variables word of mouth (WOM) (x1), brand awareness (x2), and product quality (x3) simultaneously affect the variable purchase decision (y) which is 74.7%. Based on the calculations above, it can be concluded that there is an influence of brand awareness variables (x2) and product quality (x3) on purchasing decisions. Meanwhile, there is no influence on the Word of Mouth (x1) variable on purchasing decisions. Based on the analysis above, it can be concluded that there is a simultaneous influence of the variables word of mouth, brand awareness, product quality on the purchasing decision of Mie Gacoan in Yogyakarta